Pengaruh Komisaris Independen, Komite Audit, Preferensi Risiko Eksekutif, dan Profitabilitas terhadap Penghindaran Pajak - Shinta, Shinta; Mahroji, Mahroji (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
Tax avoidance practices represent a crucial aspect of corporate governance, reflecting management's legal efforts to minimize fiscal obligations. Agency conflicts arise when the interests of management (agents) clash with those of owners (principals), particularly in terms of tax compliance and financial reporting. Based on agency theory, this study examines the empirical influence of independent commissioners, audit committees, executive risk preferences, and profitability on tax avoidance. Using a quantitative approach, secondary data were collected from the annual reports of BEI banks for the period 2021–2023 and analyzed using multiple linear regression after testing classical assumptions. The results indicate that, partially, only profitability has a significant positive effect. Independent commissioners, audit committees, and executive risk preferences do not have individual impacts. However, all four variables simultaneously significantly influence tax avoidance practices, confirming the relevance of oversight mechanisms and managerial characteristics in controlling corporate opportunistic behavior.